Global and regional burden of hospital admissions for pneumonia in older adults: a systematic review and meta-analysis - Shi, T; Denouel, A; Tietjen, AK; Lee, JW; Falsey, AR; Demont, C; Nyawanda, BO; Cai, B; Fuentes, R; Stoszek, SK; Openshaw, P; Campbell, H; et al. (Oxford University Press, 2019)
Pneumonia constitutes a substantial disease burden among adults overall and those who are elderly. We aimed to identify all studies investigating the disease burden among older adults (age, ≥65 years) admitted to the hospital with pneumonia. We estimated the hospital admission rate and in-hospital case-fatality ratio (CFR) of pneumonia in older adults, stratified by age and economic status (industrialized vs developing), with data from a systematic review of studies published from 1996 through 2017 and from 8 unpublished population-based studies. We applied these rate estimates to population estimates for 2015 to calculate the global and regional burden in older adults who would have been admitted to the hospital with pneumonia that year. We estimated the number of in-hospital pneumonia deaths by combining in-hospital CFRs with hospital admission estimates from hospital-based studies. We identified 109 eligible studies; 73 used clinical pneumonia as the case definition, and 36 used radiologically confirmed pneumonia as the case definition. We estimated that, in 2015, 6.8 million episodes (uncertainty range [UR], 5.8–8.0 episodes) of clinical pneumonia resulted in hospital admissions of older adults worldwide. The hospital admission rate increased with advancing age and was higher in men. The total disease burden was likely underestimated when using the definition of radiologically confirmed pneumonia. Based on data from 52 hospital studies reporting data on pneumonia mortality, we estimated that about 1.1 million in-hospital deaths (UR, 0.9–1.4 in-hospital deaths) occurred among older adults. The burden of pneumonia requiring hospitalization among older adults is substantial. Appropriate prevention and management strategies should be developed to reduce its impact.